PEMETAAN POTENSI PENGGUNAAN TANAH SULTAN GROUND DI KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - , DEWANTO PRASETYO AJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sultan Ground is a land which is customary owned heritage by Keraton institutions. The existence of Sultan Ground in Yogyakarta and Bantul in particular is a social and economic asset that should be preserved and maintained. Lately, there are still many of Sultan Ground which was not inventoried well by the imperial institutions and government so feared arise misunderstood. The misunderstood example there people or agencies that certified the Sultan Ground became the property of the land when it was actually the Sultan Ground. In 2012, followed by the Privileges Special Region of Yogyakarta Regulation, one of which regulated the all aspects of Sultan Ground rule of law in order to creating a more clear and definite. To that end, the project entitled âThe Potential Use Mapping of Sultan Ground in Kabupaten Bantul, Daerah Istimewa Yogyakartaâ aimed to created and display as well as present the Distribution Map and Land Use Map of Sultan Ground in Kabupaten Bantul based on the history and law of the land, with the form of presentation of spatially and non-spatial as well as compliance with the Bantul Spatial Plan. In the making of this project is using the data obtained from BPN in the form of Bantul Sultanate Ground Map of 2002, Bappeda Bantul in the form of Spatial Map a year of 2010 to 2030, Google Earth image recorded in 2013, and the land use of the data obtained from the ground. Layer editing process and digitization of data obtained from BPN using AutoCAD 2014 software. The image processing was using Google Earth for interpretation and ER Mapper 7.1 for geometric correction, and then overlayed to the map. Interpretation of types of land use classification scheme is based according PMNA/KBPN 1, 1997. Land use identification of Sultan Ground performed to check the presence and suitability with the interpretation. Land use map then adapted to Bantul Spatial Map Year 2010-2030 by means of georeferencing in Spatial Map then overlayed on land use map in ArcGIS 10. The results of this project are thematic map spread, wide frequency distribution and the number of fields, Sultan Ground land use map equipped with a pie chart along with the extensive use of land interrelated, and land use tables conformity with Bantul Spatial Map Year 2010-2030.